A2.1 A comparison of metrics to evaluate trends in antimicrobial consumption in a tertiary children's hospital. (4th October 2017) - Kwok, M; Booth, J; Konstanty, P; Standing, JF; Irwin, AD
Abstract : Background: The capacity to accurately measure and report antimicrobial consumption is an essential element of antimicrobial stewardship (AMS). Though days of therapy (DOT) and defined daily doses (DDD) are common metrics used to measure consumption, no established metric exists in children. Our aim was to model metrics of Meropenem consumption based on administration data in a tertiary children's hospital, and to analyse trends in Meropenem consumption and resistance over time. Methods: Using an established electronic prescribing system, we extracted data on all Meropenem administrations from 2010 to 2016. Meropenem susceptibility of all Enterobacteriaceae isolates was extracted over the same period. Consumption was expressed as DOT per 1000 patient-days (DOT/1000 PD), DDD per 1000 patient-days (DDD/1000 PD). Time series analysis was undertaken to explore trends in both consumption and non-susceptibility of Enterobacteriaceae to Meropenem. Results: Meropenem consumption was highly seasonal and increased over time. Between 2010 and 2016 there was an increase of 17.2% (95% CI 13.3% to 20.1%) in DOT/1000 PD. DDD and DOT showed similar seasonal variation, and similar overall increases between 2010 and 2015 (Figure 1). Resistance in E. coli increased to Piptazobactam (from 12% to 32%, p<0.001), Ceftazidime (20% to 46%, p<0.001), and Meropenem (from 0.3% to 8%, p<0.001). Discussion: Using electronic prescribing we were able to compare DDD and DOT as measures of antimicrobial consumption in children of all ages in a large tertiary children's hospital. In this single centre setting, DDD and DOT exhibited similar trends and may be considered equivalent measures. Time series analysis allows robust inferences regarding trends in Meropenem consumption and demonstrates an increase over the last 5 years. Contemporaneously there has been an increase in E. coli resistance to Piptazobactam, Ceftazidime and of significant concern, Meropenem.